The relationship between Internet Use and Students' Study Program during the Outbreak of the Covid-19 Pandemic (A Case Study: Students of Mazandaran Technical and Vocational University) - sh. Molania jolodar; M. Amiri (Fanāvarī-i āmūzish, 2022)
Background and Objectives: Students are the main part and backbone of any educational systems and universities. Due to the outbreak of the Covid-19 in 2019, it is necessary for teachers and students to use electronic tools and the Internet more than before. This has both advantages and disadvantages. As an advantage of these tools, the students can access more resources and literature from the Internet. In addition, they can listen to a lecture more and more and they do not need to go to their colleges or schools. Also, they can save time and money. On the other hand, one disadvantage can be unnecessary usage of the Internet under the pressure of studying and participating in e-learning classes, which makes it more difficult for parents to control their children. The phenomenon of excessive and unnecessary use of the Internet and cyberspace can lead to mental and educational dysfunctions of students, which is known as Internet addiction. Internet addiction was firstly studied by Young in 1988. The purpose of this study was to investigate the relationship between improper use of the Internet and the study program of students of Mazandaran Technical and Vocational University during the Covid-19 pandemic.Methods:  The research was a survey. Among about 13,500 undergraduate students of Mazandaran Technical and Vocational University in the academic year 2020-2021, 550 students were selected based on random selection. Yang’ (1998) standard questionnaire was used for eliciting the participants’ information with regard to the Internet use and a researcher-made questionnaire was used to collect the required data for the students’ study programs. The formal validity and reliability of the Internet use and students’ study program were 0.88 and 0.91, respectively. In this study, in order to investigate the relationship between independent and dependent variables, in addition to conventional statistical methods, the information sharing measurement method (Mutual Information) was used. This method not only examined the degree of linear dependence between two random variables but also measured the nonlinear dependence. This method has many applications in information theory.Results: The results showed that the total variable of the Internet use had an inverse and significant relationship with the students' study program (Pearson coefficient = -0.35). All five components of the Internet use (the effect of the Internet on work latency, preference for the Internet over work, the degree of Internet dependence, others protesting against the extreme use of the Internet and taking refuge in the Internet due to circumstances) had an inverse and significant relationship with students who enjoyed a study program. These four components could explain 17% of the variance of the students' study program. In measuring the dependence between the variables of the Internet use and study program, students were close to each other with two methods of measuring information sharing and other methods, despite minor differences.Conclusions: It seems that the dependence on and improper use of the Internet are related to the result of students' conscious or unconscious work. The result shows that among the components of the Internet use, the effect of the Internet on work latency has the strongest relationship with the students' study program. The component of others' protest against the extreme use of the Internet due to the influence of the protest of family and others on the students' study program shows a direct and positive relationship. However, with the indirect impact of other dimensions of the Internet use, the direct and positive effect on the variable of students' study program diminishes.